Efek Pemberian Ketamin Sebagai Analgesia Adjuvan Pada Pasien Pasca Operasi: A Systematic Review - Anwar, Meirisa Afifah Nurmalia (Universitas Udayana, 2022)
Postoperative pain usually is not handled properly and it may cause discomfort to the patient. The role of analgesia to relieve pain in postoperative patients then becomes very crucial. Ketamine, an NMDA antagonist, is currently gaining attention as an adjuvant analgesia in the management of acute pain. This review will discuss further about the effects of ketamine as an adjuvant analgesia in postoperative patients. Searching literature was performed on the PubMed, Cochrane, and ProQuest databases identifying journals published from 2016 to 2020 that determined the results of ketamine as an adjuvant analgesia in postoperative patients. Writing of this systematic review is based on the systematic review guidelines by the Cochrane Textbook of Systematic Review. There were 6 studies used in this review. Participants involved in this study were patients who received surgery and ketamine intervention as adjuvant analgesia. There were 907 participants who were involved in this study, ranging in age from 18 years to 65 years. There are 4 studies reporting that ketamine can reduce postoperative pain and 2 studies that report no significant effect on postoperative pain. Based on the review conducted, ketamine as an adjuvant analgesia is considered beneficial in reducing postoperative pain in several studies, but the results are not all significant. Thus, it cannot be stated that low doses of ketamine can be effective in reducing postoperative pain.